TOWARDS SUSTAINABLE WASTE MANAGEMENT: EXAMINING INDIA’S PROGRESS - Sharholy, M; K, Ahmad; Mahmood, G; Trivedi, R. C. (International Journal of Political Science and International Relations (IJPSIR), 2022)
The generation of waste is an inherent aspect of human activity, and despite significant advancements in social, economic, and environmental domains, the implementation of effective solid waste management (SWM) practices remains a substantial challenge. Municipal and industrial waste, in particular, pose severe threats to living organisms, underscoring the urgency of adopting sustainable SWM approaches as India strives for industrialization. Developed nations have successfully managed their waste through the utilization of advanced facilities, robust government institutions, and efficient bureaucracies. However, developing countries, such as India, are still in the process of transitioning towards improved waste management practices. In the face of rapid population growth, clear government policies and competent bureaucracies are imperative to address the adverse impacts of current SWM systems on public health, the environment, and the economy. This paper presents a comprehensive review of the current state of waste management in India and aims to explore various issues concerning waste streams as of the present date. The review highlights the pressing need for sustainable waste management systems and facilities to mitigate the environmental and health hazards associated with increasing waste generation. Moreover, it emphasizes the importance of effective government policies and bureaucratic competence in establishing a well-organized waste management framework in the country.